PERENCANAAN SISTEM PEMANENAN AIR HUJAN DALAM MEMENUHI KEBUTUHAN AIR DI NUSA PENIDA (Rainwater Harvesting System Planning to Meet Water Needs in Nusa Penida) - Tri Hayatining Pamungkas; Mawiti Infantri Yekti; I Gede Adi Alit Putra (Asosiasi Peneliti dan Teknisi Kehutanan dan Lingkungan Hidup Indonesia (APTKLHI), 2023)
Nusa Penida is one of several tourism areas used as a mainstay by Bali Province in accommodating tourists who want to vacation in Bali. One component to support tourism is water or water availability capacity. The lack of water resources that can be utilized, especially on two islands in Nusa Penida, namely Nusa Ceningan Island and Nusa Lembongan, requires looking for alternative water sources, one of which is rainwater sources. One method of utilizing rainwater is harvesting rainwater (PAH) using the roof of the building. The most decisive components in this technique are the roof of the building and the volume of the reservoir. The analysis showed that from the existing data, the water demand on Nusa Ceningan and Nusa Lembongan Islands during the dry six months was 48,405.5 liters per year. This water requirement can be met by using rainwater harvesting, which uses a roof area of 68.54 m2, and the harvested water is accommodated with a reservoir with a capacity of 48.41 m3.